Ten millennia of hepatitis B virus evolution - Kocher, Arthur; Papac, Luka; Barquera, Rodrigo; Key, Felix M; Spyrou, Maria A; Hübler, Ron; Rohrlach, Adam B; Aron, Franziska; Stahl, Raphaela; Wissgott, Antje; van Bömmel, Florian; Pfefferkorn, Maria; et al. (Science (New York, N.Y.), 2021)
Hepatitis B virus (HBV) has been infecting humans for millennia and remains a global health problem, but its past diversity and dispersal routes are largely unknown. We generated HBV genomic data from 137 Eurasians and Native Americans dated between ~10,500 and ~400 years ago. We date the most recent common ancestor of all HBV lineages to between ~20,000 and 12,000 years ago, with the virus present in European and South American hunter-gatherers during the early Holocene. After the European Neolithic transition, Mesolithic HBV strains were replaced by a lineage likely disseminated by early farmers that prevailed throughout western Eurasia for ~4000 years, declining around the end of the 2nd millennium BCE. The only remnant of this prehistoric HBV diversity is the rare genotype G, which appears to have reemerged during the HIV pandemic.
Keywords: molekulární evoluce; Amerika; Humans; paleontologie; Phylogeny; běloši; Evropa; Evolution, Molecular; indián nebo domorodec z Aljašky; genomika; Communicable Diseases, Emerging; American Indian or Alaska Native; Asie; White People; lidé; virus hepatitidy B; Europe; dějiny starověku; Americas; genetická variace; Genetic Variation; Hepatitis B virus; Paleontology; objevující se infekční nemoci; hepatitida B; fylogeneze; History, Ancient; Hepatitis B; Asia; Genomics; Asian People; Asijci